(untitled) (Texas Journal of Engineering and Technology, 2022)
A technique has been developed for correcting the frequency of maintenance of an internal combustion engine of motor vehicles according to a complex criterion for diagnosing the technical condition of engine oil. The dependence of the frequency of oil change of motor vehicle engines on the developed complex criterion was determined